King of Bollywood : Shah Rukh Khan and the seductive world of Indian cinema - Anupama Chopra (Warner Books, 2007)
Here is a true story of Bollywood, a sweeping portrait of a country finding its identity, a movie industry that changed the face of India, and one man's struggle to become a star. Shah Rukh Khan's larger-than-life tale takes us through the colorful and idiosyncratic Bollywood movie industry, where fantastic dreams and outrageous obsessions share the spotlight with extortion, murder, and corruption. Khan broke into this $1.5 billion business despite the fact that it has always been controlled by a handful of legendary film families and sometimes funded by black market money. As a Muslim in a Hindu majority nation, exulting in classic Indian cultural values, Khan has come to embody the aspirations and contradictions of a complicated culture tumbling headlong into American style capitalism. His story is a mirror to the greater Indian story and the underbelly of the culture of Bollywood.--From publisher description.